Political theory and international relations - Beitz, Charles R. (Princeton University Press, 1999)
"In this revised edition of his 1979 classic Political Theory and International Relations, Charles Beitz rejects two highly influential conceptions of international theory as empirically inaccurate and theoretically misleading. In one, international relations is a Hobbesian state of nature in which moral judgments are entirely inappropriate, and in the other, states are analogous to persons in domestic society in having rights of autonomy that insulate them from external moral assessment and political interference. Beitz postulates that a theory of international politics should include a revised principle of state autonomy based on the justice of a state's domestic institutions, and a principle of international distributive justice to establish a fair division of resources and wealth among persons situated in diverse national societies."--Jacket.